Towards Scalable and Robust Overlay Networks - Awerbuch, Baruch; Scheideler, Christian (6th International workshop on Peer-To-Peer Systems, IPTPS 2007, Bellevue, WA, USA, February 26-27, 2007)

A denial-of-service resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Proceedings of the Twenty-Sixth Annual ACM Symposium on Principles of Distributed Computing, PODC 2007, Portland, Oregon, USA, August 12-15, 2007)

A Denial-of-Service Resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Distributed Computing, 21st International Symposium, DISC 2007, Lemesos, Cyprus, September 24-26, 2007, Proceedings)

Distributed Computing in Sensor Systems, Third IEEE International Conference, DCOSS 2007, Santa Fe, NM, USA, June 18-20, 2007, Proceedings

SPAA 2007: Proceedings of the 19th Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Diego, California, USA, June 9-11, 2007

Overlay Networks for Peer-to-Peer Networks - W. Richa, Andrea; Scheideler, Christian (Handbook of Approximation Algorithms and Metaheuristics.)

Review of “studio d A1” and “Lagune 1” from a pronunciation perspective - Müller, Mareike (Electronic Journal of Foreign Language Teaching)

The k-Resource Problem on Uniform and on Uniformly Decomposable Metric Spaces - Bienkowski, Marcin; Kutyłowski, Jarosław (Lecture Notes in Computer Science)
We define a natural generalization of the prominent k-server problem, the k-resource problem. It occurs in metric spaces with some demands and resources given at its points. The demands may vary with time, but the total demand may never exceed k. The goal of an online algorithm is to satisfy demands by moving resources, while minimizing the cost for transporting resources. We give an asymptotically optimal O(log(min {n,k}))-competitive randomized algorithm and an O(min {k,n})-competitive deterministic one for the k-resource problem on uniform metric spaces consisting of n points. This extends known results for paging to the more general setting of k-resource. Basing on the results for uniform metric spaces, we develop a randomized algorithm solving the k-resource and the k-server problem on metric spaces which can be decomposed into components far away from each other. The algorithm achieves a competitive ratio of O(log(min {n,k})), provided that it has some extra resources more than the optimal algorithm.

Peer-to-Peer-Netzwerke - Mahlmann, Peter; Schindelhauer, Christian
Dieses Buch beschäftigt sich mit Algorithmen und Methoden der Peer-to-Peer-Netzwerke und gibt einen Einblick in die aktuelle Forschung. Ursprünglich waren Peer-to-Peer-Netzwerke nur für File-Sharing konzipiert. Mittlerweile hat sich Peer-to-Peer zum Paradigma für Rechnernetzwerke entwickelt. Ziel dieses Buches ist es, dem Leser ein grundlegendes Verständnis der Techniken hinter den aktuellen Peer-to-Peer-Netzwerken aufzuzeigen und im nächsten Schritt Algorithmen vorzustellen, die vielleicht erst in einigen Jahren umgesetzt werden. Das Buch richtet sich in erster Linie an Informatiker (Studenten ab dem 5. Semester). Aber auch interessierte Nichtinformatiker können von diesem Buch profitieren, wobei grundlegende Kenntnisse aus den Bereichen der Mathematik und Informatik vorausgesetzt werden. Die Ziele, Kernaussagen und Ergebnisse sollten jedoch auch ohne akademischen Hintergrund klar werden.

Protein intake during the period of complementary feeding and early childhood and the association with body mass index and percentage body fat at 7 y of age. - Günther, AL; Buyken, Anette; Kroke, A (Am J Clin Nutr)

Breakfast glycemic index affects subsequent daily energy intake in free-living healthy children. - Buyken, Anette; Trauner, K; Günther, AL; Kroke, A; Remer, T (Am J Clin Nutr)

How early dietary factors modify the effect of rapid weight gain in infancy on subsequent body-composition development in term children whose birth weight was appropriate for gestational age. - Karaolis-Danckert, N; Günther, AL; Kroke, A; Hornberg, C; Buyken, Anette (Am J Clin Nutr)

Early protein intake and later obesity risk: which protein sources at which time points throughout infancy and childhood are important for body mass index and body fat percentage at 7 y of age? - Günther, AL; Remer, T; Kroke, A; Buyken, Anette (Am J Clin Nutr)

Standortplanung - Betz, Stefan (Handwörterbuch der Betriebswirtschaft)

Unscharfe Produktionsmengenplanung als Instrument des Risikomanagements in Supply Chains - Betz, Stefan (Risikomanagement in Supply Chains)

Influence of particle size and concentration on the second-harmonic signal generated at colloidal surfaces - Schneider, L.; Schmid, Hans-Joachim; Peukert, W. (Applied Physics B)
Second harmonic generation (SHG) spectroscopy is a recently developed technique for the investigation of surface properties of particles. To apply the method to technical colloidal systems, the dependences of several experimental parameters on the signal have to be studied. In this work the influence of particle concentration on the SHG signal from the surfaces of colloids (polystyrene beads in a size range of 0.1 μm to 2.9 μm) is investigated. A simple model, based on Lambert–Beer’s law, to describe the measured dependences is derived. The model agrees with the experimental observations for particles smaller 1.1 μm and with a small modification also for larger particles. Based on the new model an analytical equation for determining the optimum concentration, where highest signals in colloidal SHG spectroscopy measurements are obtained, is derived.

Perspektiven für das Lehren und Lernen in der Grundschule. Theorie und Praxis der Grundschule

Lehren und Lernen im Geometrieunterricht - Hellmich, Frank (Didaktik des Unterrichts im Förderschwerpunkt Lernen. Eine Handreichung für Praxis und Studium)

Erwerb von Kompetenz im Unterricht - Hellmich, Frank (Perspektiven textiler Bildung)

Geometrie - Hellmich, Frank (Sonderpädagogik des Lernens. Handbuch Sonderpädagogik)

Augen zu und durch!? – Wie lernen angehende Grundschullehrerinnen und -lehrer im Studium? - Hellmich, Frank; Sämisch, Markus (Qualität von Grundschulunterricht entwickeln, erfassen und bewerten)

Bedingungen anschlussfähiger Bildungsprozesse von Kindern beim Übergang vom Kindergarten in die Grundschule - Hellmich, Frank (Bildungsforschung)
Erfolgreiche anschlussfähige Bildungsprozesse stellen eine wichtige Voraussetzung für die Persönlichkeits- und Kompetenzentwicklung von Kindern dar. Der Vorbereitung auf einen erfolgreichen Übergang vom Kindergarten in die Grundschule kommt dabei eine besondere Schlüsselstellung zu. Vor diesem Hintergrund wird in diesem Beitrag über eine Untersuchung berichtet, bei der 112 Vorschulkinder zu ihren Einstellungen und Erwartungen im Zusammenhang mit ihrer bevorstehenden Grundschulzeit befragt wurden. Die Ergebnisse verdeutlichen Anknüpfungspunkte für Konzepte zur Vorbereitung von Übergängen.

Möglichkeiten der Förderung mathematischer Vorläuferfähigkeiten im vorschulischen Bereich - Hellmich, Frank (Bildungsforschung)

Standards und Perspektiven für das Mathematiklernen in der Vor- und Grundschulzeit - Hellmich, Frank; Grüßing , Meike (Perspektiven für das Lehren und Lernen in der Grundschule. Theorie und Praxis der Grundschule)

Standards, Perspektiven und Tendenzen in der Grundschulpädagogik – Einleitung - Hellmich, Frank (Perspektiven für das Lehren und Lernen in der Grundschule. Theorie und Praxis der Grundschule)

„Nach dem Spiel ist vor dem Spiel!?“ – Grundschulpädagogik nach IGLU - Hellmich, Frank (Perspektiven für das Lehren und Lernen in der Grundschule. Theorie und Praxis der Grundschule)

On using data abstractions for model checking refinements - Derrick, John; Wehrheim, Heike (Acta Inf.)

Extending a Component Specification Language with Time - Metzler, Björn; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Modelchecking Correctness of Refactorings - Some Experiments - Estler, H.{-}Christian; Ruhroth, Thomas; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Assuring Consistency of Business Process Models and Web Services Using Visual Contracts - Engels, Gregor; Güldali, Baris; Soltenborn, Christian; Wehrheim, Heike (Applications of Graph Transformations with Industrial Relevance, Third International Symposium, AGTIVE 2007, Kassel, Germany, October 10-12, 2007, Revised Selected and Invited Papers)

Analysis of UML Activities Using Dynamic Meta Modeling - Engels, Gregor; Soltenborn, Christian; Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems, 9th IFIP WG 6.1 International Conference, FMOODS 2007, Paphos, Cyprus, June 6-8, 2007, Proceedings)

Refactoring Object-Oriented Specifications with Data and Processes - Ruhroth, Thomas; Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems, 9th IFIP WG 6.1 International Conference, FMOODS 2007, Paphos, Cyprus, June 6-8, 2007, Proceedings)

The Challenges of Building Advanced Mechatronic Systems - Schäfer, Wilhelm; Wehrheim, Heike (International Conference on Software Engineering, ISCE 2007, Workshop on the Future of Software Engineering, FOSE 2007, May 23-25, 2007, Minneapolis, MN, USA)

Proving Linearizability Via Non-atomic Refinement - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (Integrated Formal Methods, 6th International Conference, IFM 2007, Oxford, UK, July 2-5, 2007, Proceedings)

Global Shift – The European Union, the United States, and the Emergence of China - Gries, Thomas (50 Years of EU Economic Dynamics)

Educational Disparity and Income Inequality in Urban China - Gries, Thomas; Xue, Jinjun (The Economic Science)

Local Polynomial Estimation with a FARIMA-GARCH Error Process - Beran, Jan; Feng, Yuanhua (Bernoulli)

Identification of services --- A stakeholder-based approach to SOA development and its application in the area of production planning - Klose, Karsten; Knackstedt, Ralf; Beverungen, Daniel (Proceedings of the 15th European Conference on Information System)

Bereitstellung von Artikelstammdaten - Becker, Jörg; Winkelmann, Axel; Beverungen, Daniel; Janiesch, Christian (HMD --- Praxis der Wirtschaftsinformatik)

Measurement of learning culture: a motivational approach - Bauer, J; Rehrl, M; Harteis, Christian (Learning in the workplace--new developments)

Über die Rolle epistemischer Überzeugungen für die Gestaltung von E-Learning—eine empirische Studie bei Hochschullehrendenn - Gruber, Hans; Harteis, Christian; Hasanbegovic, Jasmina; Lehner, Franz (Neue Trends im E-Learning)

Epistemological beliefs and their impact on the practice of e-learning in companies - Harteis, Christian; Gruber, Hans; Hertramph, Herbert (Computers and advances technologies in education. Globalization of education through advanced technology)

Learning from errors in the workplace--insights from two studies in Germany and Finland - Harteis, Christian; Bauer, Johannes; Haltia, Petri (Learning in the workplace--new developments)

Die steuerliche Ungleichbehandlung von Anteilen an Kapitalgesellschaften - Müller, Jens (Finanz Betrieb)
Das Bundesverfassungsgericht hat die aktuelle Erbschaft- und Schenkungsteuer für verfassungswidrig erklärt. Verantwortlich hierfür sind insbesondere die unterschiedlichen Bewertungen der einzelnen Vermögenspositionen. In diesem Beitrag wird die steuerliche Unter- oder Überbewertung von Anteilen an Kapitalgesellschaften untersucht. Durch Sensitivitätsanalysen wird illustriert, in welchem Maß ökonomische Rahmenbedingungen die Wertlücke zwischen Steuer- und Marktwert verändern. Die Ergebnisse zeigen, dass die geltenden steuerlichen Bewertungsvorschriften in verschiedenen realistischen Szenarien selbst bei ähnlichen Unternehmenstypen zu einer Ungleichbehandlung führen.
Keywords: Anteile Kapitalgesellschaften; Rahmenbedingung; Wertlücke; steuerliche Ungleichbehandlung

Participation as predictor of responsibility in working life - Festner, Dagmar; Harteis, Christian; Kyhä, Henna; Tuominen, T (Learning in the workplace - new developments in the relation between learning and working)

Tamper Resistance of AES -- Models, Attacks and Countermeasures - Krummel, Volker

Analysis of Countermeasures Against Access Driven Cache Attacks on AES - Blömer, Johannes; Krummel, Volker (Selected Areas in Cryptography)

Cryptanalysis of Unbalanced RSA with Small CRT-Exponent - May, Alexander (Advances in Cryptology — CRYPTO 2002)

Low Secret Exponent RSA Revisited - Blömer, Johannes; May, Alexander (Lecture Notes in Computer Science)

Key Revocation with Interval Cover Families - Blömer, Johannes; May, Alexander (Selected Areas in Cryptography)

Dimension Reduction Methods for Convolution Modular Lattices - May, Alexander; Silverman, Joseph H. (Lecture Notes in Computer Science)

A Probabilistic Zero-Test for Expressions Involving Roots of Rational Numbers - Blömer, Johannes (Algorithms — ESA’ 98)

Employment Effects of International Factor Mobility - A Theoretical Approach with Heterogenous Labor - Gries, Thomas; Jungblut, Stefan (Journal of Economic Integration)

Pattern of beverage consumption and long-term association with body-weight status in German adolescents – results from the DONALD study - Libuda, Lars; Alexy, Ute; Sichert-Hellert, Wolfgang; Stehle, Peter; Karaolis-Danckert, Nadina; Buyken, Anette; Kersting, Mathilde (British Journal of Nutrition)
In the present study the relationship between the consumption of different beverage groups and body-weight status in 5 years of study participation in German adolescents was investigated. We used anthropometric and dietary data from 3 d weighed records of 244 subjects between 9 and 18 years of age participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Only subjects with at least four out of six possible weighed dietary records were considered. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of beverage consumption on body-weight status. BMI standard deviation scores (BMI-SDS) and body fat percentage (%BF) were chosen as the dependent variables. In boys, energetic beverage consumption was not associated with BMI-SDS or %BF, neither cross-sectionally nor prospectively. In girls, baseline consumption of energetic beverages did not predict baseline BMI-SDS, baseline %BF, or change in either variable over the study period. However, an increase in energetic beverage consumption over the study period was associated with an increase in BMI-SDS (+0.070 SDS/MJ increase in energetic beverage consumption; P = 0·01). Separate consideration of regular soft drinks and fruit juices revealed that, in girls, BMI-SDS increased with increased fruit juice consumption (+0·096 SDS/MJ increase in fruit juice consumption; P = 0·01), and to a lesser extent with regular soft drink consumption (+0·055 SDS/MJ increase in regular soft drink consumption; P = 0·08). In conclusion, these results suggest that an increase in energetic beverage consumption may result in weight gain, at least in adolescent girls.

DONALD News: Zuckerhaltige Getränke und Übergewicht bei Kindern. - Libuda, Lars; Alexey, U. (Monatsschriften Kinderheilkunde)

Dietary Glycemic Index, Glycemic Load, Fiber, Simple Sugars, and Insulin Resistance: The Inter99 Study: Response to Lau et al. - Buyken, Anette; Liese, A. D. (Diabetes Care)

Type 2 diabetes mellitus and risk of coronary heart disease: results of the 10-year follow-up of the PROCAM study - Buyken, Anette; von Eckardstein, Arnold; Schulte, Helmut; Cullen, Paul; Assmann, Gerd (European Journal of Cardiovascular Prevention & Rehabilitation)

Zum Umgang mit Vielfalt im haushaltsbezogenen Unterricht - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Vermittlung von Konsum- und Finanzkompetenzen für Kinder und Jugendliche - Möglichkeiten und Grenzen pädagogischen Handelns - Schlegel-Matthies, Kirsten (Der pädagogische Blick. Zeitschrift für Wissenschaft und Praxis in pädagogischen Berufen)

REVIS - Moderne Ernährungs- und Verbraucherbildung - Oepping, A.; Schlegel-Matthies, Kirsten

Grammatik der Menschenbezeichner in biographischen Kontexten - Geierhos, Michaela

Informationsextraktion aus Stellenanzeigen im Internet - Bsiri, Sandra; Geierhos, Michaela (LWA 2007: Lernen - Wissen - Adaption, Halle, September 2007, Workshop Proceedings)
Dieser Beitrag beschäftigt sich mit der Informationsextraktion aus Stellenanzeigen im französischsprachigen Web. Ziel dieser Arbeit ist es, unstrukturierte Dokumente in Repräasentationsvektoren anhand lokaler Grammatiken zu transformieren. Auf diese Weise wird es möglich, den Stellenmarkt für Jobsuchmaschinen transparenter zu gestalten, indem nur auf dem Inhalt der Anzeige in Form von Darstellungsvektoren anstatt auf unübersichtlichem Fließtext gesucht werden muss.

Program evaluation using fuzzy logic with bad smells as inputs - Delic, A.; Avdagic, Z.; Schäfer, Wilhelm; Boskovic, Dusanka; Meyer, Matthias (Proc. of the 21st International Symposium on Information, Communication and Automation Technologies (ICAT 2007), Sarajevo, Bosnia Herzegovina)

Flexible dezentrale Administration überschneidender Benutzergruppen – Informationelle Selbstbestimmung durch benutzerkontrollierte Provisionierung - Brennecke, Andreas; Finke, Stefan; König, J.; Oevel, Gudrun (Konferenzband der 20. DFN-Jahrestagung DFN2006)

Ernst Zermelo. An Approach to His Life and Work - Ebbinghaus, Heinz-Dieter; Peckhaus, Volker
Rezension: Neue Zürcher Zeitung v. 6. Juni 2007 (G. Szpiro); Ralf Bülow, “Hundert Jahre moderne Mathematik”, heise online v. 13.02.2008 (http://www.heise.de/newsticker/Hundert-Jahre-moderne-Mathematik–/meldung/103411); Mathematical Reviews 2007m:01024 (J.M. Plotkin); MAA Online 5. Juli 2007 (M. Berg); Philip J. Davis, “The Z of ZF and ZFC and ZF¬C”, SIAM News 41.1, January/February 2008; SIAM Review 50.1 (2008), 167–169; (J.W. Dawson); European Mathematical Society Newsletter June 2008, 54; The Mathematical Intelligencer 31 (2009), 79–81 (Henry E. Heatherly); Notices of the AMS 56 (2009), 823–827 (G.H. Moore); Zbl. Math. 1176.01001 (H.K. Sørensen).

Der Mathematikunterricht 53, H. 5: Schwerpunkt: Philosophie und Mathematik

Correlation Effects in Disordered Metallic Photonic Crystal Slabs - Nau, D.; Schönhardt, A.; Bauer, Ch.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Klein, M. W.; Giessen, H. (Physical Review Letters)

Lorentz model for metamaterials: Optical frequency resonance circuits - Meyrath, T. P.; Zentgraf, Thomas; Giessen, H. (Physical Review B)

Guarding our digital society's well-being - Leonardi, Stefano; Mahlmann, Peter; Meyer auf der Heide, Friedhelm; Spirakis, Paul G.; Weikum, Gerhard (e-Strategies, www.britishpublishers.com)

Ultrabroadband 50-130 THz pulses generated via phase-matched difference frequency mixing in LiIO_3 - Zentgraf, Thomas; Huber, Rupert; Nielsen, Nils C.; Chemla, Daniel S.; Kaindl, Robert A. (Optics Express)

The origin of magnetic polarizability in metamaterials at optical frequencies - an electrodynamic approach - Rockstuhl, Carsten; Zentgraf, Thomas; Pshenay-Severin, Ekaterina; Petschulat, Jörg; Chipouline, Arkadi; Kuhl, Jürgen; Pertsch, Thomas; Giessen, Harald; Lederer, Falk (Optics Express)

Babinet’s principle for optical frequency metamaterials and nanoantennas - Zentgraf, Thomas; Meyrath, T. P.; Seidel, A.; Kaiser, S.; Giessen, H.; Rockstuhl, C.; Lederer, F. (Physical Review B)

Resonance hybridization in double split-ring resonator metamaterials - Guo, Hongcang; Liu, Na; Fu, Liwei; Meyrath, Todd P.; Zentgraf, Thomas; Schweizer, Heinz; Giessen, Harald (Optics Express)

Enhanced transmission of periodic, quasiperiodic, and random nanoaperture arrays - Rockstuhl, Carsten; Lederer, Falk; Zentgraf, Thomas; Giessen, Harald (Applied Physics Letters)

Optical properties of disordered metallic photonic crystal slabs - Nau, D.; Schönhardt, A.; Christ, A.; Zentgraf, Thomas; Bauer, Ch.; Kuhl, J.; Giessen, H. (physica status solidi (a))

Dynamics and dephasing of plasmon polaritons in metallic photonic crystal superlattices: Time- and frequency-resolved nonlinear autocorrelation measurements and simulations - Utikal, Tobias; Zentgraf, Thomas; Kuhl, Jürgen; Giessen, Harald (Physical Review B)

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Why Robots Need Maps - Dynia, Miroslaw; Łopuszański, Jakub; Schindelhauer, Christian (Proc. of the 14th Colloquium on Structural Information and Communication Complexity (SIROCCO))

Competitive Maintenance of Minimum Spanning Trees in Dynamic Graphs - Dynia, Miroslaw; Korzeniowski, Miroslaw; Kutyłowski, Jarosław (Proc. of the 33rd International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM'07))

Using Mobile Relays for Ensuring Connectivity in Sparse Networks - Kutylowski, Jaroslaw

Competitive Maintenance of Minimum Spanning Trees under Stochastic Adversaries - Kutylowski, Jaroslaw

Wort/Spiele. Drama – Film – Literatur - Eke, Norbert Otto

Tiere, Texte, Spuren

„Zwischen Utopie und Realität. Die ‚Idealstadt’ Jülich als Ausdruck des frühneuzeitlichen Ordnungsdenkens“ - Seng, Eva- Maria (Jülicher Geschichtsblätter Bd. 73)

Jörg Held (um 1454-1527), Petrarca-Meister, Vogelschau der Stadt Augsburg - Seng, Eva- Maria (Geschichte der bildenden Kunst in Deutschland, Bd. 4 Spätgotik und Renaissance)

Grausame Spiegel. Lenaus Blick zurück nach vorn: Die Albigenser. Freie Dichtungen - Eke, Norbert Otto (Von Sommerträumen und Wintermärchen. Versepen im Vormärz)

Tiere, Texte, Spuren (Vorwort) - Eke, Norbert Otto; Geulen, Eva (Tiere, Texte, Spuren)

Im „deutschen Zauberwald“. Spiegel- und Kippfiguren des Antisemitismus in deutschsprachiger Gegenwartsliteratur - Eke, Norbert Otto (Literarischer Antisemitismus nach Auschwitz)

„Nichts, was einen Anfang hatte, ist unendlich.“ Robert Menasses Arbeit an der Differenz – Die Zerstörung der Welt als Wille und Vorstellung. Frankfurter Poetikvorlesungen - Eke, Norbert Otto (Was einmal wirklich war. Zum Werk Robert Menasses)

Das ‚kleine Sagen’ und das ‚große Sagen’. Herta Müllers Gegenschrift - Eke, Norbert Otto (Walter-Hasenclever-Gesellschaft. Jahrbuch 2005/2006)

Schreckbilder: Die Revolution als Aufstand der ‚schwarzen Männer’ - Eke, Norbert Otto (Das Unterhaltungsstück um 1800. Literaturhistorische Konfigurationen – Signaturen der Moderne. Zur Geschichte des Theaters als Reflexionsmedium von Gesellschaft, Politik und Ästhetik)

A CUDA-Supported Approach to Remote Rendering - Lietsch, Stefan; Marquardt, Oliver (Proc. Int. Symp. on Visual Computing (ISVC))

Comparing Fault Tolerance Mechanisms for Self-Organizing Resource Management in Grids - Voss, Kerstin (Proc. Int. Conf. on Semantics, Knowledge and Grid (SKG))

Gaining Users' Trust by Publishing Failure Probabilities - Battré, Dominic; Djemame, Karim; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on Security and Privacy in Communications Networks (SecureComm))

Increasing the Reliability of Wireless Sensor Networks with a Unit Testing Framework - Beutel, Jan; Plessl, Christian; Woehrle, Matthias

AssessGrid, Economic Issues Underlying Risk Awareness in Grids - Voss, Kerstin; Djemame, Karim; Gourlay, Iain; Padgett, James (Proc. Int. Worksh. on Grid Economics and Business Models (GECON))

Enhance Self-managing Grids by Risk Management - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Computational Steering of Interactive and Distributed Virtual Reality Applications - Lietsch, Stefan; Zabel, Henning; Berssenbruegge, Jan (Proc. ASME Computers and Information in Engineering Conference (CIE))

Gather and Prepare Monitoring Data for Estimating Resource Stability - Birkenheuer, Georg; Majlender, Peter; Nitsche, Holger; Voss, Kerstin; Weber, Elmar (Proc. Cracow Grid Workshop (CGW))

Verteilte Berechnung und Darstellung automobiler Scheinwerfer - Berssenbrügge, Jan; Lietsch, Stefan (Proc. Worksh. Augmented & Virtual Reality in der Produktentstehung)